Pengaruh E-Commerce terhadap Perilaku Konsumtif - Kirei Zhihan Putri; Naila Zahara; Sri Mulyeni (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study focuses on the use of E-Commerce among students at Universitas Nasional Pasim, particulary in the Faculty of Economics. The primary objective of this research is to identify the impact of E-Commerce usage on students’ consumptive behavior. Using a quantitative method, data was collected through the distribution of questionnaires. The analysis of the questionnaires, employing a validity test, confirmed that all data obtained were valid and suitable for further investigation. The findings reveal that consumptive behavior significantly impacts human life, including financial, academic, and social aspects. In the long term, consumptive behavior can negatively affect their future. Therefore, it is essential for students to enhance their awareness of the importance of a simply lifestyle, financial planning, and responsible management of their needs. The results indicate that 61,8% of the variation in consumptive behavior can be explained by the influence of E-Commerce.